(untitled) (CIPEEX, 2025)
This research analyzes public policies on basic sanitation in the municipality of Senador Canedo, from the perspective of the right to the city. The central problem lies in the unequal access to sanitation services, such as drinking water, sewage, solid waste management and urban drainage, compromising the exercise of this right. The general objective is to evaluate the effectiveness of these policies in the municipality. Specifically, it seeks to: (a) characterize the municipality of Senador Canedo in socio-economic and environmental terms relevant to sanitation; (b) examine the Master Plan and the Municipal Basic Sanitation Plan, identifying guidelines and targets; and (c) investigate the implementation of policies, assessing their impact on the population’s quality of life and the right to the city. The methodology is qualitative, involving document analysis and interviews with public managers and representatives of civil society. The justification for the study is based on the importance of understanding the impact of basic sanitation policies on urban development and the promotion of decent living conditions. The results indicate that, although there have been regulatory advances, the effectiveness of the policies in Senador Canedo is limited by a lack of adequate infrastructure and insufficient investment. Problems such as precarious sanitation, solid waste management and urban drainage still affect the population’s quality of life. The study concludes that infrastructure modernization, greater coordination between levels of government and active community participation are essential to promote the right to the city.